Coach mid-season replacement and team performance in professional team sport. Evidence from Spanish Soccer - Lago-Penas, C.; Casais-Martinez, L.; Rey-Eiras, E.; Lago-Ballesteros, J. (World Congress of Performance Analysis of Sport VIII, 2008)
The coaching carousel or turnover is an extreme but frequently occurring phenomenon in soccer. Among the reasons for firing a coach, the most common is the existence of a shock-effect: the new coach would be able to motivate the players better and therefore to improve results. This study investigates the relationship between team performance and coach change over time. The results of the empirical analysis suggest that team performance under the authority of the new coach improves significantly compared with that under the old coach in the short term but this impact is negligible in the long term. There results point out that the favourable shortterm impact on team performance after a coach change should be explained by the psychological and motivational effect on players provided by the coach turnover (Pfeffer & Davis-Blake, 1986; Fabianic, 1994; McTeer & White 1995 and Bennet et al., 2003). These results demonstrate the positive influence of coach change on team performance and support empirically the arguments of the common-sense theory. For a team experiencing a run of bad results, a change of coach may provide the stimulus required to break the sequence.